(\(\dfrac{a}{b}\))\(^3\)=\(\dfrac{1}{1000}\) và b-a=36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(bx^2=ay^2\Rightarrow\dfrac{x^2}{a}=\dfrac{y^2}{b}=\dfrac{x^2+y^2}{a+b}=\dfrac{1}{a+b}\)
\(\Rightarrow\left(\dfrac{x^2}{a}\right)^{1000}=\left(\dfrac{y^2}{b}\right)^{1000}=\left(\dfrac{1}{a+b}\right)^{1000}\)
\(\Rightarrow\dfrac{x^{2000}}{a^{1000}}=\dfrac{y^{2000}}{b^{1000}}=\dfrac{1}{\left(a+b\right)^{1000}}\)
\(\Rightarrow\dfrac{x^{2000}}{a^{1000}}+\dfrac{y^{2000}}{b^{1000}}=\dfrac{1}{\left(a+b\right)^{1000}}+\dfrac{1}{\left(a+b\right)^{1000}}=\dfrac{2}{\left(a+b\right)^{1000}}\)
a, A= 1/2. (2/1.2.3+2/2.3.4+2/3.4.5+...+2/18.19.20) A=1/2. (1/1.2-1/2.3+1/2.3-1/3.4+1/3.4-1/4.5+...+1/18.19-1/19.20) A=1/2. (1/1.2-1/19.20) A=1/2. 189/380 A= 189/760
Ta có:
\(\dfrac{a}{3}=\dfrac{b}{5}\Leftrightarrow a=\dfrac{3b}{5}\)
Khi đó:
\(b^2-a^2=36\Leftrightarrow b^2-\dfrac{9b^2}{25}=36\\ \Leftrightarrow\dfrac{16b^2}{25}=36\Leftrightarrow b^2=\dfrac{225}{4}\Leftrightarrow b=\dfrac{\pm15}{2}\)
Với \(b=\dfrac{15}{2}\) suy ra: \(a=\dfrac{3b}{5}=\dfrac{3}{5}.\dfrac{15}{2}=\dfrac{9}{2}\)
Với \(b=\dfrac{-15}{2}\) suy ra: \(a=\dfrac{3b}{5}=\dfrac{3}{5}.\dfrac{-15}{2}=\dfrac{-9}{2}\)
a: 51/56=1-5/56
61/66=1-5/66
mà -5/56<-5/66
nên 51/56<61/66
b: 41/43<1<172/165
c: \(\dfrac{101}{506}>0>-\dfrac{707}{3534}\)
a) Vì A=\(\dfrac{15^{16}+1}{15^{17}+1}\) < 1
\(\Rightarrow\dfrac{15^{16}+1}{15^{17}+1}< \dfrac{15^{16}+1+14}{15^{17}+1+14}=\dfrac{15^{16}+15}{15^{17}+15}\) \(=\dfrac{15\left(15^{15}+1\right)}{15\left(15^{16}+1\right)}\) \(=\dfrac{15^{15}+1}{15^{16}+1}\)
Vậy A<B
b) A=\(\dfrac{2006^{2007}+1}{2006^{2006}+1}>1\)
\(\Rightarrow\dfrac{2006^{2007}+1+2005}{2006^{2006}+1+2005}\)
= \(\dfrac{2006^{2007}+2006}{2006^{2006}+2006}\)
= \(\dfrac{2006\left(2006^{2006}+1\right)}{2006\left(2006^{2005}+1\right)}\)
= \(\dfrac{2006^{2006+1}}{2006^{2005}+1}\)
Vậy A>B
Ta có \(\left(\dfrac{a}{b}\right)^3=\dfrac{1}{1000}\)
\(\Rightarrow\left(\dfrac{a}{b}\right)^3=\left(\dfrac{1}{10}\right)^3\)
\(\Rightarrow\dfrac{a}{b}=\dfrac{1}{10}\)
\(\Rightarrow\dfrac{a}{1}=\dfrac{b}{10}\)
Áp dụng tính chất dãy tỉ số bằng nhau
\(\dfrac{a}{1}=\dfrac{b}{10}=\dfrac{b-a}{10-1}=\dfrac{36}{9}=4\)
\(\Rightarrow\dfrac{a}{1}=4\Rightarrow a=4.1=4\)
\(\dfrac{b}{10}=4\Rightarrow b=4.10=40\)
Vậy a=4, b=40